PENGARUH PERMAINAN BOY-BOYAN UNTUK MENINGKATKAN MINAT SISWA PUTRI DALAM PEMBELAJARAN SEPAKBOLA KELAS VII SMPN 1 CILAMAYA WETAN - Afiat, Intan; Asep Suherman; Nana Suryana Nasution (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of the researcher in making this thesis is to answer the formulation of the problem in the study, namely the problem in this study is